Preparation method and application of composite paper-based material for filtering micro-nano plastics

By loading TEMPO on the surface of the filter paper with oxidized nanocellulose and cross-linking treatment, nanocellulose/filter paper composite materials were prepared, which solved the problems of low filtration flux and unenvironmental materials in the prior art, and achieved high efficiency and environmental protection micro-nano plastic filtration effect.

CN118223330BActive Publication Date: 2025-02-11NANJING FORESTRY UNIV

Patent Information

Application Number
CN202410513645.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-26
Publication Date
2025-02-11
Estimated Expiration
2044-04-26

AI Technical Summary

Technical Problem

The prior art has problems such as low filtration flux and unenvironmental materials in micro-nano plastic filtration, making it difficult to effectively remove micro-nano plastic pollution in water.

Method used

The nanocellulose/filter paper composite paper-based material was prepared as a filter medium for micro-nanoplastics by loading TEMPO on the surface of the filter paper and connecting the nanocellulose with the filter paper fibers by glutaraldehyde cross-linking treatment.

Benefits of technology

It has achieved efficient filtration of micro-nano plastics, with a filtration efficiency of 98%, a filtration flux of 783.53L*m-2*h-1*bar-1, and has maintained high-efficiency filtration performance after 10 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118223330B_ABST
    Figure CN118223330B_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a composite paper-based material for filtering micro-nano plastics, and belongs to the technical field of biomass chemical industry. The invention adopts a vacuum filtration method to load TEMPO-oxidized nanocellulose on the surface of filter paper, and connects nanocellulose and filter paper fibers through glutaraldehyde cross-linking treatment to obtain a nanocellulose filter paper composite paper-based material. The nanocellulose loading method of the invention not only increases the number of recycling times of paper-based materials and enhances the practical application performance of paper-based materials, but also realizes the controllable regulation (filtration efficiency and filtration flux) of the composite material on the filtering performance of micro-nano plastics by controlling the nanocellulose loading amount. The composite paper-based material has excellent filtering effect on micro-nano plastics, is environmentally friendly, is easy to produce, can be recycled, and can be widely promoted and used.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of paper-based filter materials, and specifically relates to a preparation method of a nano cellulose / filter paper composite paper-based filter material and application thereof in micro-nano plastic filtration. Background Art

[0002] Today, pollutants in the ecological environment include PM2.5, heavy metal ions, organic dyes, micro-nano plastics, viruses, etc. Among them, micro-nano plastics are one of the top ten environmental problems that need to be solved globally. They are widely present in various natural environments such as oceans, fresh water and soil. Micro-nano plastics have also been found in human blood, proving that they have achieved dynamic circulation between the atmosphere, land, water environment and organisms. Therefore, there is an urgent need for a material that can be used to filter micro-nano plastics. Filtration is the process of purifying a fluid through a certain medium under certain external conditions. It can be applied to many systems, such as solid-liquid, solid-gas, etc. The basic principle of filtration is that under external conditions, the fluid in the suspension passes through the filter medium and its impurities are intercepted by the filter medium, thereby separating the impurities from the fluid. Filter media are often divided into three types: woven materials, porous solids and stacked media. Common woven materials are filter cloths and filter screens woven from natural or synthetic fibers, metal wires, etc., but their pore sizes are relatively large. Porous solids and stacked media are mainly high-porosity, small-pore materials such as ceramics, aerogels, and ultrafiltration membranes. The diversity of filter media can meet the needs of different fluids.

[0003] Generally speaking, the common filtration medium for micro-nano plastics in water is often a membrane system, but the membrane system has problems such as low filtration flux and environmentally unfriendly materials. The common filtration medium for micro-nano plastic filtration is membrane material and porous solid material. For example, Pizzichetti et al. (ARPPizzichetti, C.Pablos, C. -Fernández, K.Reynolds, S.Stanley, J.Marugán, Case Studies in Chemical and Environmental Engineering 3(2021)) studied the filtration performance of polycarbonate, polycellulose acetate, and polytetrafluoroethylene for microplastics. With the assistance of a high-pressure vacuum pump, the filtration efficiency of all membranes exceeded 94%. For example, Zhu et al. (Gaojian Zhu, Jie Wang, Xiaotong Wang, Yuqian Liu, Weibing Wu, Huining Xiao, Liulian Huang, Hongqi Dai, Xuelian Zhou, and Huiyang Bian. ACS Sustainable Chemistry & Engineering 2023 11(38), 13928-13938) prepared amino-modified CNF aerogel for the separation of micro-nanoplastics in water, but its filtration flux was only 32.6 L / m 2 / h.

[0004] Filter paper is a common filter material. Its raw materials are renewable resources, the manufacturing process is simple, and it has little pollution to the environment. The excellent hydrophilicity and large pore size of commercial filter paper give it a large filtration flux, but it can only intercept large-sized solids in the fluid. In addition, the mechanical properties and recyclability of filter paper are poor, making it difficult to apply to large-scale water treatment processes. Therefore, it is necessary to enhance the small particle capture performance and wide adaptability of filter paper on the basis of environmental friendliness and high filtration flux. Nanocellulose is an environmentally friendly material with a surface rich in hydrophilic groups, small size, and large specific surface area. In recent years, there have been many in-depth studies on nanocellulose. Some studies have shown that loading nanocellulose on the surface of filter paper to form a nanocellulose membrane can effectively improve the filtration efficiency of the filter paper. For example, Wang Zhiguo et al. (CN 107583472 A) used TEMPO oxidation combined with mechanical method to prepare nanocellulose and filtered it to the filter paper surface to improve the filtration efficiency of the filter paper for bovine serum albumin; Zhang et al. (Zhang, F., Ren, H., Shen, L. et al. Cellulose 24, 2913–2924 (2017).) used CNF aerogel microspheres loaded on the surface of filter paper to enhance the hydrophobic / oleophobic properties of the filter paper, and the composite filter paper can be used to separate the oil phase and the water phase in the fluid; Huang (Y. Huang, H. Zhan, D. Li, H. Tian, ​​C. Chan, Journal of Membrane Science 591 (2019)) et al. used epichlorohydrin to cross-link cellulose nanocrystals and filter paper fibers and fixed them on the surface of the filter paper, giving the filter paper excellent oil-water separation performance and expanding its application scenarios.

[0005] Therefore, nanocellulose can be used as a reinforcing material to improve the filtration efficiency, filtration flux and applicability of filter paper, so that the filter paper can capture small particles of micro-nano plastics and meet the needs of different fluids and the diversity of filtration media.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The first purpose of the present invention is to provide a method for preparing a nanocellulose composite material with filter paper as the substrate, by cross-linking TEMPO-oxidized nanocellulose and ordinary commercial filter paper with glutaraldehyde solution to prepare an environmentally friendly filter paper-based nanocellulose composite material as a filter medium for micro-nano plastic pollution in water bodies.

[0008] The second purpose of the present invention is to provide an application of a nanocellulose composite material in the filtration of micro-nano plastics. By changing the nanocellulose loading amount to reduce the pore size of the filter paper-based nanocellulose composite material, the filtration efficiency of micro-nano plastics in water is enhanced and the number of recycling times is increased, thereby achieving the purpose of expanding its application scenarios.

[0009] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0010] A method for preparing a composite paper-based material for filtering micro-nano plastics comprises the following steps: loading TEMPO-oxidized nanocellulose on the surface of filter paper by vacuum filtration, and connecting the nanocellulose and filter paper fibers by glutaraldehyde cross-linking treatment to obtain a nanocellulose / filter paper composite paper-based material.

[0011] Furthermore, the preparation method of the composite paper-based material for filtering micro-nano plastics comprises the following steps:

[0012] (1) soaking filter paper in HCl solution, drying and preparing porous filter paper;

[0013] (2) loading the TEMPO-oxidized cellulose nanofiber solution onto the porous filter paper of step (1) by vacuum filtration;

[0014] (3) Soaking the composite paper-based material in step (2) in a glutaraldehyde solution to prepare a nanocellulose-loaded composite paper-based material.

[0015] Furthermore, in step (1), the concentration of the HCl solution is 0.2 M and the immersion time is 5 min.

[0016] Furthermore, in step (1), the drying temperature of the filter paper after soaking is 60° C. and the drying time is 24 hours.

[0017] Furthermore, in step (2), the concentration of the cellulose nanofiber solution is 0.05%, and the loading amount on the filter paper surface does not exceed 1.00 g / m 2 .

[0018] Furthermore, in step (2), the paper-based composite materials with different nanocellulose loadings are dried at 60° C. for 48 h.

[0019] Furthermore, in step (3), the mass proportions of the substances in the glutaraldehyde solution are: 3% glutaraldehyde, 96% ethanol, 1% hydrochloric acid; and the reaction time is 6h.

[0020] Furthermore, the composite paper-based material prepared by any of the above methods is used in filtering micro-nano plastics.

[0021] Furthermore, the types of micro-nano plastics used for filtration include: PS, PP and PET; the concentration does not exceed 100 ppm.

[0022] Furthermore, the sizes of micro-nano plastics are PS: 100nm~10μm, PP: 21.7~250.8μm, and PET: 4.3~260.4μm.

[0023] Compared with the prior art, the advantages of the present invention are as follows:

[0024] (1) The present invention uses ordinary filter paper as the substrate, the substrate material is widely available, the production cost is low, and it has a high economic advantage.

[0025] (2) The present invention uses ordinary filter paper as the substrate and nanocellulose as the loading layer, and adopts vacuum filtration to achieve loading, which can achieve the purpose of environmental friendliness and simple preparation.

[0026] (3) The present invention has an excellent filtering effect on plastics of different types, sizes and concentrations by regulating the pore size of the filter paper-based nanocellulose composite material, and has a wide range of applications in the filtration treatment of plastic pollution in water bodies.

[0027] (4) The filter paper-based nanocellulose composite material obtained by the present invention can achieve a filtration efficiency of 98% for plastics (2 μm COOH-PS) and a filtration flux of 783.53 L*m -2 *h -1 *bar -1 After 10 cycles, it still has plastic filtration effect, the filtration efficiency is increased to 99%, and the filtration flux is 463.42L*m -2 *h -1 *bar -1 .

[0028] (5) The filter paper-based nanocellulose filter material prepared in the present invention can become a high-efficiency, high-throughput, multi-cycle water pollution filtration medium. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a surface morphology characterization diagram of filter paper-based nanocellulose composites;

[0030] Among them, (af) are FE-SEM images of filter paper, 0-filter paper, 0.25-filter paper, 0.50-filter paper, 0.75-filter paper, and 1.00-filter paper, respectively, with a scale bar of 200 μm; (g) is a paper surface image of filter paper, 0.50-filter paper, and 1.00-filter paper; (h) is an average pore size image of filter paper, 0-filter paper, 0.25-filter paper, 0.50-filter paper, 0.75-filter paper, and 1.00-filter paper.

[0031] Figure 2 This is an analysis chart of the filtration performance of filter paper-based nanocellulose composite materials on different types of polystyrene plastics;

[0032] Among them, the filtration efficiency and filtration flux of (ac)0.75-filter paper for different types and sizes of polystyrene plastics were analyzed. Plastic concentration = 50ppm.

[0033] Figure 3 This is an analysis chart of the filtration performance of paper-based composite materials with different nanocellulose loadings on carboxyl polystyrene;

[0034] Among them, (a) the coating amount is 0.75g / m 2 Filtration efficiency and filtration flux of filter paper for microplastics at different concentrations. (be) Fluorescence microscope images of microplastics at concentrations of 25ppm, 50ppm, 75ppm and 100ppm. (fi) Fluorescence microscope images of the filtrate after filtering microplastics at concentrations of 25ppm, 50ppm, 75ppm and 100ppm. (jm) Fluorescence intensity before and after filtration of microplastics at concentrations of 25ppm, 50ppm, 75ppm and 100ppm. The microplastic used was COOH-PS, 2μm. (n) Filtration efficiency and filtration flux analysis of filter paper with different nanocellulose loadings. The plastic used was COOH-PS, 2μm. (op) Cycle filtration efficiency and filtration flux analysis of filter paper with different loadings, with the number of cycles being 1-10 times. The plastic used was COOH-PS, 2μm.

[0035] Figure 4 This is an analysis chart of the filtration performance of filter paper-based nanocellulose composite materials on polypropylene and polyethylene terephthalate;

[0036] Among them, (a) chemical structure and size analysis images of PP (top) and PET (bottom); (b) standard curve fitting images of PP and PET; (c) scanning electron microscope image of PP, scale bar = 500 microns; (d) scanning electron microscope image after PP is filtered by modified filter paper, scale bar = 200 microns; (e) scanning electron microscope image of PET, scale bar = 500 microns; (f) scanning electron microscope image after PET is filtered by modified filter paper, scale bar = 200 microns; (g) filtration efficiency and filtration flux diagram of PP and PET; (h) actual picture before and after PP filtration; (i) actual picture before and after PET filtration. DETAILED DESCRIPTION

[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments.

[0038] Example 1

[0039] The preparation method of the filter paper-based nanocellulose composite material comprises the following specific steps:

[0040] (1) Filter paper pore modification

[0041] Use hydrochloric acid soaking method to make pores on filter paper. The concentration of hydrochloric acid is 0.2M. Soak the filter paper in hydrochloric acid solution for 5 minutes. After taking it out, rinse the surface of the filter paper until the pH of the cleaning solution is ≥6. Figure 1 (a) Figure 1 (b) is the SEM image of the filter paper before and after modification. The image shows that the pores on the surface of the filter paper soaked in hydrochloric acid become larger. In addition, Figure 1 (h) It can be found that the average pore size of the filter paper changes before and after modification. The average pore size of the filter paper soaked in hydrochloric acid becomes larger than that of the original filter paper.

[0042] (2) Preparation of nanocellulose solution

[0043] TEMPO-oxidized nanocellulose was purchased from Tianjin Wood Elf Biotechnology Co., Ltd. The usage amounts were 0.25, 0.50, 0.75, and 1.00 g / m 2 The nanocellulose was diluted to 8 mL and stirred at 600 rpm for 2 h to disperse the nanocellulose and obtain a uniform nanocellulose solution.

[0044] (3) Preparation of filter paper-based nanocellulose composites

[0045] The nanocellulose solution obtained in step (2) is filtered by vacuum filtration onto the surface of the modified filter paper obtained in step (1). At room temperature, the modified filter paper coated with nanocellulose is soaked in a glutaraldehyde solution containing 3% glutaraldehyde, 96% ethanol, and 1% hydrochloric acid for 6 hours to chemically cross-link the nanocellulose and the filter paper fibers to obtain a nanocellulose / filter paper composite paper-based material. Figure 1 (cf) are SEM images of filter papers with different nanocellulose loadings. It can be seen from the figure that as the loading increases, the pore structure on the filter paper surface is covered. When the loading exceeds 0.75 g / m 2 When the filter paper surface pores are completely covered. Figure 1 (g) is a photo of the filter paper before and after loading with nanocellulose. The loading layer can be clearly seen on the surface of the filter paper loaded with nanocellulose. Figure 1 (h) The effect of nanocellulose loading on the average pore size of the filter paper can also be seen. As the loading increases, the average pore size of the filter paper gradually decreases and finally decreases to 2.5 μm.

[0046] Example 2

[0047] Filter paper-based nanocellulose composite material filtration PS experiment: The cellulose prepared in Example 1 and dried at 60°C was loaded with 0.75 g / m 2The nanocellulose composite paper-based material was used as the filter element of the filter device, and an iron stand was used to stabilize the filter device. PS suspensions with sizes of 100 nm, 2 μm, and 10 μm were diluted to 50 ppm, respectively, and the PS suspensions were dispersed by ultrasonic treatment. The filtration test was carried out under a stable pressure of 0.1 bar. 10 mL of the dispersed PS suspension was poured into the filter device and the timing was started. When the filtration was completed, the timing was stopped and the filtrate was collected. The filtration area, filtration time, and filtrate PS concentration of the filter device were combined with the known PS volume and PS concentration to calculate the filtration efficiency (FE) and filtration flux (F):

[0048]

[0049]

[0050] Where C0 is the initial microplastic concentration (ppm); C1 is the microplastic concentration after filtration (ppm); V is the liquid volume (L); S is the effective filtration area (m 2 ) ; t is the filtration time (h); P is the negative pressure applied to the filtration device during the filtration process (bar).

[0051] The filter paper-based nanocellulose composite material prepared in Example 1 was measured using the above-mentioned measurement method. The results are as follows: Figure 2 As shown in (a), it is not difficult to find that the PS size has a great influence on the filtration efficiency and filtration flux of the filter paper-based nanocellulose composite material. The larger the PS size, the higher the filtration efficiency and the larger the filtration flux. The filtration performance of the composite paper-based material for PS with a size ≥ 2μm has a significant advantage over that of small-sized PS.

[0052] Example 3

[0053] The filter paper-based nanocellulose composite material was used to filter COOH-PS. The method was the same as in Example 2. Since TEMPO-oxidized nanocellulose was negatively charged, the effect of electrostatic repulsion on PS filtration was studied. The results are shown in Table 2. Figure 2 As shown in (b), the filtration efficiency and filtration flux of filter paper-based nanocellulose composite materials for COOH-PS of different sizes are not the same. When the COOH-PS size is larger than 2 μm, the filtration efficiency exceeds 95%, and the larger the PS size, the greater the filtration flux.

[0054] Example 4

[0055] The filter paper-based nanocellulose composite material was used to filter NH2-PS. The method was the same as in Example 2. Since TEMPO-oxidized nanocellulose was negatively charged, the effect of electrostatic attraction on PS filtration was studied. The results are shown in Table 2. Figure 2As shown in (c), it can be found that the filtration performance of the filter paper-based nanocellulose composite material for PS with amino groups is similar to its filtration performance for other types of PS. As described in Examples 2 and 3, the size will affect its filtration efficiency and flux.

[0056] Table 1: Comparison of experimental data on the filtration performance of filter paper-based nanocellulose composite materials for PS, COOH-PS, and NH2-PS in Examples 2-4

[0057]

[0058] From Table 1, we can see that Figure 2 The comprehensive analysis of the data in (ac) shows that the filter paper-based nanocellulose composite material has the best filtration performance for COOH-PS. When the COOH-PS size is 2 μm, the filtration efficiency is 98.5% and the filtration flux is 738.53 L*m -2 *h -1 *bar -1 When the COOH-PS size is 10 μm, the filtration efficiency is 95.9% and the filtration flux is 2062.6 L*m -2 *h -1 *bar -1 .

[0059] Example 5

[0060] In order to study the effect of different COOH-PS suspension concentrations on the filtration performance of filter paper-based nanocellulose composites, 25 ppm, 50 ppm, 75 ppm and 100 ppm COOH-PS suspensions were selected for filtration operation. The experimental method was the same as that in Example 2. The results are shown in FIG. Figure 3 (a). Figure 3 It can be clearly seen from (a) that the filtration efficiency of the filter paper-based nanocellulose composite material exceeds 97.5%, but the higher the concentration, the lower the filtration flux, and the filtration flux increases from 887.8 L*m -2 *h -1 *bar -1 Reduced to 775.4L*m -2 *h -1 *bar -1 .

[0061] Example 6

[0062] In order to study the effect of different nanocellulose loadings on the filtration performance of composite paper-based materials for microplastics, the nanocellulose loading was selected to be 0.25 g / m 2 , 0.50g / m 2 , 0.75g / m 2 and 1.00g / m 2The filter paper-based nanocellulose composite material was subjected to a filtration experiment, and the experimental method was the same as in Example 2. The results are as follows Figure 3 (n). Figure 3 (n) It can be seen that the nanocellulose loading amount will also affect the filtration performance of the composite paper-based material. The larger the nanocellulose loading amount, the higher the filtration efficiency of the composite paper-based material, but the lower the filtration flux.

[0063] The results of Examples 5 and 6 above show that the concentration of COOH-PS and the amount of nanocellulose loaded have a great influence on the filtration performance (filtration efficiency and filtration flux) of the filter paper-based nanocellulose composite material. By comparing the concentration of 50 ppm COOH-PS and the nanocellulose loading of 0.75 g / m 2 The filter paper-based nanocellulose composite material was used to carry out a cyclic filtration experiment on microplastics.

[0064] Example 7

[0065] The filter paper-based composite materials with different nanocellulose loading amounts were subjected to a cyclic filtration experiment on 50 ppm, 2 μm COOH-PS. The filtration method was the same as in Example 2. It is worth noting that the filter paper-based nanocellulose composite materials after one cycle need to be rinsed and air-dried before the next cycle.

[0066] The results are as follows Figure 3 (o) and Figure 3 (p) As shown. The filter paper-based nanocellulose composite material can filter COOH-PS with a size of 2 μm for 10 cycles, and as the number of cycles increases, the filtration efficiency of the composite material gradually increases and the filtration flux gradually decreases. When the nanocellulose loading is 0.75 g / m 2 and 1.00g / m 2 When the filtration efficiency exceeded 95%, and finally reached 99%, the nanocellulose loading was 0.75 g / m 2 The tenth filtration flux of the composite paper-based material is 463.42L*m -2 *h -1 *bar -1 The high filtration efficiency and high flux reflect the excellent circulation filtration effect of the filter paper-based nanocellulose composite material.

[0067] Example 8

[0068] Nanocellulose loading is 0.75 g / m 2 The filtration experiment of PP by the filter paper-based nanocellulose composite material was carried out in the same manner as in Example 2, but the PP size was changed. The PP suspensions with sizes of 21.65 μm, 83.65 μm and 250.76 μm were diluted to 50 ppm and dispersed by ultrasonic treatment. The results are shown in FIG. Figure 4(g) The filter paper-based nanocellulose composite material has good filtration performance for PP, with a filtration efficiency of 92.5% and a filtration flux of 236.0 L*m -2 *h -1 *bar -1 .

[0069] Example 9

[0070] Nanocellulose loading is 0.75 g / m 2 The filtration experiment of the filter paper-based nanocellulose composite material on PET was carried out in the same manner as in Example 2, but the PET size was changed. The PET suspensions with sizes of 4.33 μm, 65.64 μm and 260.36 μm were diluted to 50 ppm, and the PET suspensions were dispersed by ultrasonic treatment. The results are shown in FIG. Figure 4 (g)s. The filter paper-based nanocellulose composite material has excellent filtration performance for PET, with a filtration efficiency of 96.1% and a filtration flux of 577.1L*m -2 *h -1 *bar -1 .

[0071] The above Examples 8 and 9 prove that the filter paper-based nanocellulose composite material has an excellent effect on the removal of different types of microplastics (PP and PET), with a filtration efficiency of more than 90%, and a filtration flux of up to 577 L*m for PET. -2 *h -1 *bar -1 .

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Application of a nanocellulose-loaded composite paper-based material as a filter element of a filter device in filtering micro-nano plastic pollutants COOH-PS or NH2-PS in water, wherein the nanocellulose-loaded composite paper-based material is prepared by the following steps: (1) Soak the filter paper in a 0.2 M hydrochloric acid solution for 5 min. After taking it out, rinse the surface of the filter paper until the pH of the cleaning solution is ≥6; (2) Usage: 0.75 g / m 2 The nanocellulose was diluted to 8 mL and stirred at 600 rpm for 2 h to disperse the nanocellulose and obtain a uniform nanocellulose solution; (3) Using vacuum filtration, the nanocellulose solution obtained in step (2) is filtered onto the surface of the modified filter paper obtained in step (1); at room temperature, the modified filter paper coated with nanocellulose is soaked in a glutaraldehyde solution having a ratio of 3% glutaraldehyde, 96% ethanol, and 1% hydrochloric acid for 6 hours to chemically cross-link the nanocellulose and the filter paper fibers to obtain a loading of 0.75 g / m 2 Nanocellulose-loaded composite paper-based materials; The process of using the nanocellulose-loaded composite paper-based material as a filter element in filtering micro-nano plastic pollutants in water is as follows: 2 Nanocellulose composite paper-based material was used as the filter element of the filtration device, and an iron stand was used to stabilize the filtration device; the water containing COOH-PS or NH2-PS was dispersed into a suspension by ultrasonic treatment; the filtration test was carried out at a stable pressure of 0.1 bar; the sizes of COOH-PS and NH2-PS were both 2 μm, and the concentrations were both 50 ppm.

2. Application of a nanocellulose-loaded composite paper-based material as a filter element of a filter device in filtering micro-nano plastic pollutants PS in water bodies, wherein the nanocellulose-loaded composite paper-based material is prepared by the following steps: (1) Soak the filter paper in a 0.2 M hydrochloric acid solution for 5 min. After taking it out, rinse the surface of the filter paper until the pH of the cleaning solution is ≥6; (2) Usage: 0.75 g / m 2 The nanocellulose was diluted to 8 mL and stirred at 600 rpm for 2 h to disperse the nanocellulose and obtain a uniform nanocellulose solution; (3) Using vacuum filtration, the nanocellulose solution obtained in step (2) is filtered onto the surface of the modified filter paper obtained in step (1); at room temperature, the modified filter paper coated with nanocellulose is soaked in a glutaraldehyde solution having a ratio of 3% glutaraldehyde, 96% ethanol, and 1% hydrochloric acid for 6 hours to chemically cross-link the nanocellulose and the filter paper fibers to obtain a loading of 0.75 g / m 2 Nanocellulose-loaded composite paper-based materials; The process of using the nanocellulose-loaded composite paper-based material as a filter element in filtering micro-nano plastic pollutants in water is as follows: 2 Nanocellulose composite paper-based material was used as the filter element of the filtration device, and an iron stand was used to stabilize the filtration device; the water containing PS was dispersed into a suspension by ultrasonic treatment; the filtration test was carried out at a stable pressure of 0.1 bar; the PS size was 2 μm and the concentration was 50 ppm.

3. Application of a nanocellulose-loaded composite paper-based material as a filter element of a filter device in filtering micro-nano plastic pollutants PP or PET in water, wherein the nanocellulose-loaded composite paper-based material is prepared by the following steps: (1) Soak the filter paper in a 0.2 M hydrochloric acid solution for 5 min. After taking it out, rinse the surface of the filter paper until the pH of the cleaning solution is ≥6; (2) Usage: 0.75 g / m 2 The nanocellulose was diluted to 8 mL and stirred at 600 rpm for 2 h to disperse the nanocellulose and obtain a uniform nanocellulose solution; (3) Using vacuum filtration, the nanocellulose solution obtained in step (2) is filtered onto the surface of the modified filter paper obtained in step (1); at room temperature, the modified filter paper coated with nanocellulose is soaked in a glutaraldehyde solution having a ratio of 3% glutaraldehyde, 96% ethanol, and 1% hydrochloric acid for 6 hours to chemically cross-link the nanocellulose and the filter paper fibers to obtain a loading of 0.75 g / m 2 Nanocellulose-loaded composite paper-based materials; The process of using the nanocellulose-loaded composite paper-based material as a filter element in filtering micro-nano plastic pollutants in water is as follows: 2 The nanocellulose composite paper-based material was used as the filter element of the filtration device, and an iron stand was used to stabilize the filtration device. The water containing PP or PET was dispersed into a suspension by ultrasonic treatment. The filtration test was carried out at a stable pressure of 0.1 bar. The concentration of PP or PET was 50 ppm.

Citation Information

Patent Citations

  • Bacterial cellulose nanofiber composite filtration membrane and preparation method thereof

    CN107335346A

  • Preparation method of nanocellulose / filter paper composite filter membrane material

    CN107583472A

  • Nano-fiber coating antibacterial film for biological pharmacy and preparation method thereof

    CN110314557A

Cited By

  • Cellulose fiber-based sandwich structure filter material for removing micro-plastics and preparation method of cellulose fiber-based sandwich structure filter material

    CN121648646A